Research on the Disturbance Observer Based Generalized Wind/Solar Intergration Control Strategy - Xuemeng ZHANG; Rui WANG; Dazhong MA; Kai DU (Zhongguo dianli)
With the high proportion of distributed renewable energy sources, such as photovoltaic and wind power, connected to the micro-grid, the uncertainty of its power generation output brings significant pressure to the safe and stable operation of the micro grid. Based on this, a disturbance observer based on generalized wind/solar isomorphic model is proposed. Firstly, by establishing the analogy model between the state equation of the interface rectifier and the state equation of the photovoltaic interface Boost circuit, the equivalent model of the isomorphic photovoltaic/wind turbine with single input and single output is proposed, so that the wind turbine and photovoltaic can achieve the consistency of the generalized model. Secondly, in order to solve the problem of partially unknown state variables caused by the output uncertainties of distributed energy such as photovoltaic and wind turbines, a continuous-time disturbance observer is introduced to control the equivalent generalized Boost model. When the illumination or wind speed changes, the disturbance observer can quickly follow the change. At the same time, with the passage of time, the disturbance observer can achieve no-difference adjustment, so as to control the equivalent generalized Boost model. The purpose of eliminating the partial state unknown caused by disturbance is achieved. Furthermore, the output voltage, current and power of a stable wind/photovoltaic hybrid system can be obtained by using a voltage-current double disturbance observer, and the output can quickly reach the given value. Finally, the effectiveness and reliability of the proposed method are verified by simulation.